Pengaruh Recovery Ice Bath Terhadap Penurunan Kelelahan pada Atlet UKM Hockey Outdoor Putri Universitas Negeri Surabaya - Riski Amilia; Mohammad Faruk (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to examine the effect of appliying the Recovery Ice Bath on reducing fatigue in female outdoor hockey athletes of Universitas Negeri Surabaya. The research employes a pre-experimental method with a One Group Pretest- Posttest Desing. A total of 12 female athletes from Universitas Negeri Surabaya were selected as the study sample. Data were collected through RPE (Rate of Percevied Exertion) quistionnaires, Vas (Visual Analogue Scale) questionnaires,and heart rate meassurements. The analysis of pretest and posttest heart rate values yielded a significant result (0,000 <0,05). Indicating a statistically significant effect of the Recovery Ice Bath. Similarly, the RPE and VAS questionnaire results showed significant values (0,002<0,05 for RPE and VAS), suggesting a substantial impact of the Recovery Ice Bath on reducing fatigue levels and pain in female outdoor hockey athletes at Universitas Negeri Surabaya. In conclusion, the application of the Recovery Ice Bath significantly influences fatigue reduction in outdoor hockey athletes.athletes who underwent ice baths experienced a faster decline in physical fatigue and muscle soreness. Moreover, ice baths proved effective in accelerating muscle recovery, as evidenced by the reduced Delayed Onset Muscle Soreness (DOMS) after engaging in intense physical activity.